'Interlocalization': Can India be a party to the process?. (December 2016) - Kumar, Rajesh
'Interlocalization' has been witnessed as a new praxis in international communication which is all about horizontal flow of knowledge, culture, tradition, know-how and so on, among countries of the world, free from any form of hegemony and domination as against what has been observed in the case of 'globalization' and also in 'glocalization'. This study is an attempt to understand and analyse this phenomenon in the Indian context, and it revolves around two possible broad catalysts of the interlocalization process: (1) India's communication business alliances and (2) transnational networking among Indian diaspora communities. The article finds that India's communication business alliances around the world have not yet reached a level to provide the desired impetus to the interlocalization process, although it is gaining momentum. But a highly encouraging scenario is presented in the case of Indian diaspora networking and its implications for the interlocalization process.